Penerapan Model Pembelajaran Team Assisted Individualization (TAI) Dalam Meningkatkan Pemahaman Konsep Matematika - Misastri, Mia; Wirayuda, Ricky Purnama; Syarbaini, Syarbaini (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: Research This done with objective For analyze understanding draft mathematics competence number with using the Learning Model Team Assisted Individualization (TAI) for students class IV Madrasah Ibtidaiyah Al-Hidayah Kebon IX Muaro Jambi. Methodology: Deep data study This in the form of quantitative and qualitative data which is analyzed in a manner descriptive and data obtained through stages observation as much as 2 cycles with sample as many as 18 students. Main Findings: After done 2 cycles obtained happen enhancement understanding draft improved mathematic using learning models Team Assisted Individualization (TAI). enhancement results from understanding draft mathematics competence number student by 26.73%. Novelty/Originality of this study: Updating from study This is related research with enhancement understanding draft mathematics competence number with using the Learning Model The previous Team Assisted Individualization (TAI).